Germans, Poland, and Colonial Expansion to the East
X, 201 p. 7 illus.
Keywords: This incisive collection probes the history of colonialism within Europe and posits that Eastern Europe was in fact Germany s true "colonial" empire. Through a series of interdisciplinary essays ranging from 1850 to the European Union of today, this collection explores the idea that Germany s relationship with Poland and Eastern Europe had many similarities to the practice of "overseas" colonialism. As the contributing scholars aptly demonstrate, the history of Germany s relationship with Poland contains all the trappings of the classic colonial encounter, from its structures of power and control, racism and cultural chauvinism, to the implementation of wholesale scientific experimentation in a "lawless" environment.